Harmony of Artistic Thinking and Philosophical Observation in Islamic Lyrics - Otajon Norov (International Journal on Integrated Education, 2022)
This article deals with the formal-methodological, ideological-literary features of Islamic poetry. In particular, the unprecedented changes in artistic thinking that took place at the end of the twentieth century and on the eve of the new century made it possible to radically reform the level of philosophical coverage. As a result, it was observed in detail that poetry and being poet is a huge issue and a responsibility.